Characterization of cytomegalovirus lung infection in Non-HIV infected children (2014)
Cytomegalovirus (CMV) is a prevalent pathogen in the immunocompromised host and invasive pneumonia is a feared complication of the virus in this population. In this pediatric case series we characterized CMV lung infection in 15 non-HIV infected children (median age 3 years; IQR 0.2–4.9 years), using current molecular and imaging diagnostic modalities, in combination with respiratory signs and symptoms. The most prominent clinical and laboratory findings included cough (100%), hypoxemia (100%), diffuse adventitious breath sounds (100%) and increased respiratory effort (93%). All patients had abnormal lung images characterized by ground glass opacity/consolidation in 80% of cases. CMV was detected in the lung either by CMV PCR in bronchoalveolar lavage (82% detection rate) or histology/immunohistochemistry in lung biopsy (100% detection rate). CMV caused respiratory failure in 47% of children infected and the overall mortality rate was 13.3%. Conclusion: CMV pneumonia is a potential lethal disease in non-HIV infected children that requires a high-index of suspicion. Common clinical and radiological patterns such as hypoxemia, diffuse adventitious lung sounds and ground-glass pulmonary opacities may allow early identification of CMV lung infection in the pediatric population, which may lead to prompt initiation of antiviral therapy and better clinical outcomes.